Commognitive View: Analysis Of Students' Work Results In Using Definite Integrals To Solve Contextual Problems - Laksminto Emanuel, Endrayana Putut; Dewi Soewardini, Herfa Maulina; Meilantifa (LPPM Universitas Bina Bangsa, 2025)
The purpose of this study is to describe students’ commognitive processes when solving contextual problems on definite integrals related to the area between curves. The research method was carried out through several stages, namely preparation, data collection, analysis, and drawing conclusions. The research subjects were ten students from a private university in Indonesia who were asked to solve a contextual mathematics problem within 30 minutes, specifically on definite integrals to determine the area bounded by two curves. Based on their work, one student was selected as the main subject to be analyzed using a commognitive approach and interviewed in depth to obtain more detailed information. The results of the study showed that the subject was able to translate the problem statements into mathematical form accurately. The subject was also able to use mathematical terms and symbols correctly (words use), illustrate the given conditions into graphs appropriately (visual mediators), and apply problem-solving steps systematically based on prior knowledge (routines). In addition, the subject was able to draw correct conclusions supported by valid mathematical arguments. Based on these findings, it can be concluded that students are capable of solving contextual mathematics problems successfully. Furthermore, it is expected that students can improve their understanding of course materials so that they are able to solve given problems more optimally and support the achievement of learning objectives.